2007
DOI: 10.1158/1078-0432.ccr-06-2184
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of O6-Methylguanine DNA Methyltransferase and Loss of Heterozygosity on 19q and/or 17p Are Overlapping Features of Secondary Glioblastomas with Prolonged Survival

Abstract: Purpose: Recent data suggest that methylation of the DNA repair gene O 6 -methylguanine DNA methyltransferase (MGMT), by increasing the chemosensitivity of glioblastoma multiforme, is significantly associated with improved prognosis. Results in contradiction with these findings, however, are present in the literature and the clinical and genetic context framing MGMT methylation is poorly characterized. Experimental Design: To address these issues, we have investigated the MGMT methylation status, clinical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
97
5
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(119 citation statements)
references
References 38 publications
10
97
5
7
Order By: Relevance
“…This finding is in agreement with published reports, showing that 45-68% of the glioblastomas have methylated MGMT promoters. (Hegi et al, 2004(Hegi et al, , 2005Eoli et al, 2007;Dunn et al, 2009;Jha et al, 2010). In our study, all oligoastrocytomas as well as nearly all oligodendrogliomas (93.3%) were methylated.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This finding is in agreement with published reports, showing that 45-68% of the glioblastomas have methylated MGMT promoters. (Hegi et al, 2004(Hegi et al, , 2005Eoli et al, 2007;Dunn et al, 2009;Jha et al, 2010). In our study, all oligoastrocytomas as well as nearly all oligodendrogliomas (93.3%) were methylated.…”
Section: Discussionsupporting
confidence: 53%
“…We found that gain of chromosome arm 7p, was more frequent in unmethylated than in methylated gliomas (75.0% vs. 40.4%, P < 0.05). Similarly, Eoli et al (2007) observed that EGFR amplification was more common in unmethylated than in methylated glioblastomas, even if the difference was not statistically significant. In contrast to this, Jha et al (2010) did not find a significant association of EGFR amplification with MGMT hypermethylation in glioblastomas.…”
Section: Discussionmentioning
confidence: 93%
“…The dependency of MGMT on the expression levels of mGlu3 receptors might help to explain the controversial data on the correlation between MGMT promoter methylation and patients' survival. [34][35][36][37][38][39][40] Our data may pave the way to a new strategy in the pharmacological treatment of malignant gliomas because mGlu3 receptor antagonists could be added to temozolomide or other DNA-alkylating agents for the optimization of adjuvant chemotherapy. The evidence that a combined treatment with temozolomide and LY341495 was still efficacious in restraining tumor growth when initiated 45 days after cell implantation in mice is particularly promising for translation into medical practice because of the long interval between onset and treatment of malignant gliomas.…”
Section: Discussionmentioning
confidence: 87%
“…Recently Eoli et al, in [4], found significant correlations between MGMT promoter methylation status and magnetic resonance (MR) imaging features. Motivated by these findings, this research presents an automated method for predicting the methylation status of the GBM based on texture analysis of T2, FLAIR and T1-postcontrast MRI scans.…”
Section: Introductionmentioning
confidence: 99%